O estudo do ouvinte e da audiência em pesquisas sobre comportamento verbal: uma análise de publicações a partir da perspectiva skinneriana - Floriano, Renan Nobre (2015)
In Verbal Behavior (1957), BF Skinner proposes a thorough analysis of verbal behavior by specifying the relationship between the speaker's behavior and the listener's behavior. Despite this, the speaker's behavior has been more emphasized and studied The aim of this study was to analyze the bibliographic production carried out by behavior analysts about the listener's behavior, as a mediator of consequences and while audience to the speaker's behavior, from the year of publication of Verbal Behavior and work through both articles published in international journals as JEAB, JABA, The Behavior Analyst and TAVB as in national journals as REBAC and RBTCC. It was analyzed 70 articles, of which 62 dealt with the listener as a mediator of consequences, while 7 audience and one treated both concepts. It was observed that articles about the listener's behavior (listener and audience) began to markedly small measure, the first published 26 years after the Verbal Behavior. Over the years the publications of articles geared to the study of these concepts have been increasing, as a result of the contribution of authors like Caio F. Miguel, R. Douglas Greer and Anna Ingeborg Petursdottir. With regard to the type of research, it was noted a balance between theoretical and conceptual research and experimental research and among the experimental research it was observed that the listener's behavior has been studied both as an independent variable as the dependent variable. Moreover, in both types of research the listener's behavior was studied more as a central object than a secondary object. Finally, there is the listener's behavior was notorious presence on subject-matters such as the relationship between the repertoire of the listener and the speaker, stimulus equivalence, verbal operant tact and naming. Summarizing the development of this field of research, it highlights two assertions of Skinner himself (1957/1992) regarding the understanding of verbal behavior that influenced a timid start, but also contributed to advances in research: on the one hand, verbal behavior was to focus the explicit individual speaker and postulated by Skinner (19957/1992), on the other hand, there is the need for the listener's behavior be closely analyzed so that a complete understanding of verbal behavior is achieved